Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini) - Huang, Sunbin; Zhou, Jiajun; Tian, Mingyi; Faille, Arnaud (European Journal of Taxonomy, 2021)
Three new species of the genus Guiodytes Tian, 2013 are described from the limestone caves of Guangxi Zhuang Autonomous Region, southern China: Guiodytes weii Huang & Faille sp. nov. and Guiodytes yueliangensis Huang & Tian sp. nov. from Dapo Dong and Huang Dong caves, respectively, in Huanjiang County, northernmost Guangxi; Guiodytes inexpectatus Tian & Zhou sp. nov. from the Zhuzhu Dong cave in Longzhou County, southwestern Guangxi. All of the six known species of Guiodytes are endemic to Guangxi, ranging from the southwest to the northernmost. A modified key to species and a distribution map for Guiodytes are provided.